2021
DOI: 10.1007/s13205-021-02905-6
|View full text |Cite
|
Sign up to set email alerts
|

Use of nanotechnology in combating coronavirus

Abstract: Recent COVID-19 pandemic situation caused due to the novel severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) affected global health as well as economics. There is global attention on prevention, diagnosis as well as treatment of COVID-19 infection which would help in easing the current situation. The use of nanotechnology and nanomedicine has been considered to be promising due to its excellent potential in managing various medical issues such as viruses which is a major threat. Nanoparticles have s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 202 publications
0
12
0
Order By: Relevance
“…Drug delivery and drug design can use nanomedicine, a branch of science that deals with particles at the nanoscale [ 242 ]. Low permeability, insolubility, painful injections, prolonged hospitalization, and unfavorable side effects are just a few of the limitations of the conventional delivery system.…”
Section: Novel Strategies For Leishmaniasis and Chagas Disease Treatm...mentioning
confidence: 99%
“…Drug delivery and drug design can use nanomedicine, a branch of science that deals with particles at the nanoscale [ 242 ]. Low permeability, insolubility, painful injections, prolonged hospitalization, and unfavorable side effects are just a few of the limitations of the conventional delivery system.…”
Section: Novel Strategies For Leishmaniasis and Chagas Disease Treatm...mentioning
confidence: 99%
“…Studies have demonstrated that AgNPs <25 nm in size were 12 times more active toward HIV-1 compared to silver ions, ,, and their antiviral activity remained constant up to 150 days when the concentration was higher than 2.1 mg/L . In a review article, Gharpure and Ankamwar provided comprehensive insights into the functionalization of metal-based nanoparticles by introducing organic groups, such as sulfonated, succinic acid functionalized, thiol functionalized, and sialic acid functionalized groups. These included the modification of β-diketo acid coated AuNPs, ZnO-NPs encapsulated with polyethylene glycol (PEG), and MoS 2 -grafted thiolated surfactants. These reports suggested that the conjugation of functional groups grafted onto textiles could improve the poor adhesion of inorganic compounds with the fiber surface.…”
Section: Antiviral Textile Materialsmentioning
confidence: 99%
“…There is a global focus on the prevention, diagnosis, and treatment of COVID-19 infection, which will help alleviate the current situation. The antiviral properties of CDs are relatively new, and recent studies have shown that they are resistant to human coronaviruses, including SARS-CoV-2, and have great potential for antiviral therapy [255] (Table 7). Yu et al reported a 4-aminophenylboronic acidsynthesized CD with excellent antiviral properties and biocompatibility against HSV-1.…”
Section: Anti-virusmentioning
confidence: 99%